Differences in Mineral Contents of Apple Leaves Associated with Fruiting and Non-Fruiting of Biennial Bearing Trees - Akca, Yasar; Brohi, Abdulresit; Savas, Erdinc (Asian Journal of Chemistry, 2016)
The relationships between differences of mineral content and biennial bearing in 'Amasya' apple cv was determined. The ‘Amasya’ apple cultivar was grafted on the M.9, MM.106 and MM.111 clones and on the seedling rootstocks were planted in 2 × 2, 4 × 4, 6 × 6 and 6 × 6 m densities, respectively. The contents of leaf N, Ca, Mg, Fe, (Ca + Mg)/K, N/K and Ca/K were found higher in fruiting trees than in non-fruiting trees. Ca and Mg contents of leaves of grafted trees on M.9 were higher than MM.106, MM.111 and seedling rootstocks. Significant differences (P < 0.01) were found for K, Cu, Zn content, and N/K, (Ca + Mg)/K and Ca/K ratio of mature leaves according to used rootstocks. It is generally agreed that an increase in bearing results in an increase in leaf N, Ca and Mg. The results for P and K for fruiting and non-fruiting trees are inconclusive.